(untitled) (CAHIERS MAGELLANES-NS, 2024)
These days, green marketing is very popular in the corporate sector. Remarketing and packaging of current items that fit these requirements have already started under this plan. Organizations dedicated to green marketing development have made it possible for companies to co-brand their goods under a certain line. However, some have overlooked other factors and overemphasized environmental friendliness. Businesses can now co-brand their products on a given line because of to green marketing development organizations; yet, some have praised environmental friendliness while disregarding others. This article delves into the notion of green marketing and examines the obstacles and prospects faced by companies who implement it. The article concludes that green marketing is still in demand and provides an explanation for why businesses implement it. Green items are generally understood to be recyclable and environmentally or ecologically friendly. That being said, individual perspectives regarding eco-friendly items may differ. This essay discusses the differences between conventional and green marketing as well as green marketing strategies and golden guidelines. Consequently, a new market dubbed the "green market" has emerged as a result of the introduction of green products. Finally, discusses the nature of sustainable development and green marketing while outlining its advantages and disadvantages.